Understanding of Basic Particle Nature of Matter Concepts by Secondary School Students Following an Intervention Programme - Treagust, David; Chandrasegaran, Arulsingam; Halim, L.; Ong, E.; Zain, A.; Karpudewan, M. (Springer, 2013)
Grades 10 and 11 students’ (N=172) understanding of particle theory concepts was assessed using the Particle Theory Diagnostic Instrument (PTDI), consisting of 11 two-tier multiple-choice items in a pretest–posttest design after implementing an intervention instructional programme. The intervention programme involving eight lessons of about 45-min duration each included teacher demonstrations and student practical activities followed by class discussions to explain students’ observations. The 11 items assessed understanding in three key conceptual categories: (1) intermolecular spacing in matter (CC1), (2) the influence of intermolecular forces on changes of state (CC2), and (3) diffusion in liquids and gases (CC3), using a quantitative methodology. There was a statistically significant improvement in overall mean scores among students from the pretest (M=4.08, SD=1.79) to the posttest [M=6.04, SD=2.49, t (171)=10.10, p<0.001]. However, the students did not display a good understanding about the concepts in the three conceptual categories: only 30.8% of students correctly answered all four items in CC1, 7.0% correctly answered all three items in CC2, and 16.3% correctly answered all four items in CC3.